The Influence of Rewards on Perceptions, Competence, and Sensory and Imaginative Immersion of Malaysian Digital Traditional Games - Fazilah Hibadullah, Cik; ChePa, Noraziah; Azzah Abu Bakar, Nur; Hussain, Azham (International Journal of Engineering and Technology, 2018)
Rewards in games are among the essential features to attract players to engage with the game. Prominent scholars claimed that rewards have positive influences to game engagement.Â Despite the importance of rewards in digital games, none of the existing Malaysian digital traditional games incorporated rewards in the games. Â Therefore, this study is conducted to investigate the influence of rewards on digital games engagement which focusing on perceptions, competence, and sensory and imaginative immersion on one of the Malaysian digital traditional games, Congkak.Â The existing Congkak has been enhanced by incorporating rewards.Â Fifty respondents among the millennials were involved in the experiment to measure the influence of rewards using Game Experience Questionnaire (GEQ).Â Findings revealed that all constructs tested demonstrate positive influence of rewards on game engagement.Â The findings serve as a guideline to game developers to improve the games in order to foster better engagement of Malaysian digital traditional games.Â